PEMBERIAN AIR KELAPA MUDA TERHADAP KELELAHAN KERJA PADA BURUH ANGKUT PASAR TANJUNG KABUPATEN JEMBER - Pusponegoro, Rizqi Dwi; Pujiati, Rahayu Sri; Hartanti, Ragil Ismi (Jurnal Ilmu Kesehatan Masyarakat, 2019)
Work fatigue is one of the safety and health issues that can be a risk factor for accidents at work. Based on the preliminary study conducted by researcher in the Tanjung Traditional Market, transporter workers did repetitive work which is transporting goods by climbing up and down the stairs without using any tools. That caused their jobs are at risk of fatigue. Coconut water containing electrolyte ions needed by the body when dehydration. This study aimed to analyze the effect of giving coconut water to work fatigue on transporter workers. This research use quacy experimental research method with nonequivalent control group design. In this study, there were 32 research subjects divided into 2 groups, the experimental group and control group. The experimental group that was given 600 ml of coconut water, while the control group was given in the form of mineral water as placebo. Work fatigue was measured using Reaction Timer. The results of work fatigue measurements showed that the average has decreased over 42.3 milliseconds in the experimental group and 4.9 milliseconds in the control group.